Usefulness of Gd‐EOB‐DTPA‐enhanced MR imaging in the evaluation of simple steatosis and nonalcoholic steatohepatitis. Issue 5 (21st November 2012) - Wu, Zhuo; Matsui, Osamu; Kitao, Azusa; Kozaka, Kazuto; Koda, Wataru; Kobayashi, Satoshi; Ryu, Yasuji; Minami, Tetsuya; Sanada, Junichiro; Gabata, Toshifumi
Abstract Purpose: To evaluate the usefulness of gadolinium ethoxybenzyl diethylenetriaminepentaacetic acid (Gd‐EOB‐DTPA)‐enhanced MR imaging (EOB‐MRI) in differentiating between simple steatosis and nonalcoholic steatohepatitis (NASH), as compared with MR in‐phase/out‐of‐phase imaging. The correlations between the MR features and histological characteristics were preliminarily investigated. Materials and Methods: From April 2008 to October 2011, 25 patients (13 simple steatosis and 12 NASH) who underwent both EOB‐MRI and in‐phase/out‐of‐phase imaging were analyzed. The hepatobiliary‐phase enhancement ratio and signal intensity loss on opposed‐phase T1‐weighted images (fat fraction) were compared between the simple steatosis and NASH groups. In the simple steatosis and NASH groups, the correlations between enhancement ratio and histological grade/stage were explored. In the NASH group, fat fraction was correlated with the steatosis score. Results: The enhancement ratio in NASH was significantly lower than that in simple steatosis (P = 0.03). In the simple steatosis and NASH groups, the enhancement ratio was significantly correlated with the fibrosis stage (r = −0.469, P = 0.018). Fat fraction in NASH was strongly correlated with the steatosis score (r = 0.728, P = 0.007). Conclusion: In simple steatosis and NASH, the hepatobiliary‐phase enhancement ratio of EOB‐MRI showed significant association with fibrosis stage, and may be a useful discriminating parameter compared with the fat fraction measured by in‐phase/out‐of‐phase imaging. J. Magn. Reson. Imaging 2012;37:1137–1143. © 2012 Wiley Periodicals, Inc.